The Interplay Between Internet Gaming Disorder and Depressive Syndrome: A Study of Online Gamers in Berastagi District, Karo Regency, North Sumatra - Dita Lestari Surbakti; Hera Vanesa Sihombing (International Journal on ObGyn and Health Sciences, 2023)
This research explores the dynamic relationship between Internet Gaming Disorder (IGD) and depressive syndrome within the online gaming community in the Berastagi District, situated in Karo Regency, North Sumatra. The study adopts a mixed-methods approach, combining quantitative surveys and qualitative interviews, to unravel the complex interplay, cultural nuances, and temporal dynamics of these phenomena. Participants, selected through purposive sampling, undergo a comprehensive baseline assessment, including demographic information, gaming habits, and standardized measurements of IGD and depressive symptoms. Regular follow-up surveys, conducted longitudinally, track changes in gaming behavior and mental health outcomes over time. Qualitative interviews further illuminate subjective experiences and cultural influences within the Berastagi gaming community. The study reveals a bidirectional relationship between IGD and depressive symptoms, emphasizing the nuanced nature of their interplay. Cultural and regional factors emerge as influential elements, shaping individuals' experiences within the gaming community. Methodologically, the integration of quantitative and qualitative data enriches the understanding of the phenomena under investigation. The findings contribute to both research and practical applications, offering insights for future investigations and guiding the development of culturally sensitive interventions. As the digital landscape continues to evolve, this study serves as a beacon, navigating the complexities of Internet Gaming Disorder and depressive syndrome in the unique cultural context of Berastagi District, North Sumatra.